Profil Kreativitas Mahasiswa Calon Guru dalam Membuat Mainan Fisika - Nuroso, Harto; Kurniawan, Wawan (Jurnal Penelitian Pembelajaran Fisika, 2022)
Creativity is a pattern of student behavior that is active, has great curiosity, cannot be silent about one thing, and has the urge to develop in oneself and others. This study aims to describe the creativity of student physics teacher candidates through physics toy project-based learning. Physics toys are chosen by the students themselves with the minimum requirement that they are made of one used material. Students are required to explain what physics concepts can be explained through the toy. The result is that 75% of students make toys from bottled drinking water and 83% of the videos are uploaded on YouTube. The level of creativity of students is classified as creative with an average score of 2.1. This level of creativity still needs to be improved to produce highly creative and excellent teacher candidates.Keywords: creativity, physics toys, project-based learning.